Aesthetic functions in men's fabric and fashion designs - Asaad Ati Halil Saad Al-Moussawi ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
Fabric and fashion designs are clearly influenced by the social and economic environment and the developments taking place in the field of evaluation. This has shaped the designer's ability to devise systems and relationships. This achieves new functions resulting from his own awareness of the components from which he derives the beauty of the design idea. Thus, the research problem was defined. According to the following question: What are the aesthetic functions in men's fabric designs? With the aim of revealing the achievement of aesthetic functions in men's fabric and fashion designs, the research was determined objectively. Studying the aesthetic functions in printed designs for men's fabrics and fashion. The designs available in the markets of Baghdad, within the time period: (2024-2025. The theoretical framework included four topics that dealt with: (1)The concept of Aesthetic values.(2): It dealt with the aesthetic functions in design.(3) : The aesthetics of the visual attributes in design. The research procedures included the research methodology followed, which is content analysis from the descriptive method. The research community, which amounted to (16) models of fabric designs and men’s fashion available in the markets of Baghdad. The sample was chosen intentionally, represented by four models at a rate of (25%) of the research sample. Research findings and conclusions: The aesthetic function is determined by the combination of the overall benefit of the design. It reflects the values ​​of society and the era. Aesthetic judgments are linked to the performance of a specific function in the design product. The research concludes with a list of sources.